A low dose of benzo(a)pyrene during prepuberty in male rats generated immediate oxidative stress in the testes and compromised steroidogenic enzymes/proteins - Jorge, Bárbara C. [UNESP]; Reis, Ana C.C. [UNESP]; Stein, Julia [UNESP]; Paschoalini, Beatriz R. [UNESP]; Bueno, Jéssica N. [UNESP]; da Silva Moreira, Suyane [UNESP]; Godoi, Alana R. [UNESP]; Fioravante, Vanessa C. [UNESP]; Martinez, Francisco E. [UNESP]; Pinheiro, Patrícia F.F. [UNESP]; Arena, Arielle C. [UNESP] (Elsevier, 2024)
The prepubertal period is crucial for sexual development and any alterations can interfere with the reproductive system in adulthood. The aim of this study was to evaluate how Benzo(a)pyrene (BaP) can affect the testes during the prepubertal period. Juvenile male Wistar rats were divided into a control (corn oil + DMSO) and a BaP-group (0.1 μg/kg/day), exposed to BaP for 31 days (gavage), and all parameters were evaluated on postnatal day (PND) 54. Leukocyte counts were decreased. Histological analyses of the testes revealed that height and seminiferous tubules diameters (STDs) were reduced, tubular dynamics were altered, and Leydig cell atrophy was evident in the BaP-group. The testosterone concentration was decreased while FSH levels increased within the BaP-exposed group. Steroidogenic enzymes in the testes were decreased, but steroidogenic acute regulatory protein was not altered. The expression of gstp1 and ckit enzymes was decreased. Reduced glutathione (GSH) and superoxide dismutase (SOD) were increased, whereas malondialdehyde (MDA) was decreased in the testes. In conclusion, BaP or its metabolites causes low systemic toxicity; however, it adversely influences testicular function by disrupting the hormonal axis, unbalancing testicular antioxidative, and blocking the action of the steroidogenic mechanisms.
Keywords: BaP; Environmental pollutant; Polycyclic aromatic hydrocarbon; Reproductive toxicity; Steroidogenesis